Rare earth (RE: Nd, Dy, Ho, Y, Yb, and Sc) aluminosilicates for joining silicon carbide components. Issue 4 (2nd May 2017) - Herrmann, Marion; Ahmad, Sarfraz; Lippmann, Wolfgang; Seifert, Hans‐Jürgen; Hurtado, Antonio
Abstract: Six different types of glass 12.18 RE2 O3 ‐22 Al2 O3 ‐65.82 SiO2 (mol %) where RE: Nd, Dy, Ho, Y, Yb, and Sc were tested for joining silicon carbide (SiC) components. The different types of glass vary in their thermal properties but they are similar in their behavior for the joining process when a laser‐based heating technology was used. The quality of the joints was characterized by microscopic analysis, mechanical tests, and measurements of tightness. Annealing experiments were conducted at temperatures in the range of the glass transition and crystallization allowing an assessment of the compositions for usability as glass and as glass‐ceramic interlayers. Five of the investigated compositions can be recommended for application up to temperatures of 900°C. The Y‐ and Yb‐based compositions guarantee a high joint quality at temperatures up to 1200°C. The high temperature assessment was based on tightness and microstructural analyses of the joints after the annealing procedures. The results can be transferred to joining processes with lower heating and cooling rates.